2015
DOI: 10.1016/j.sjbs.2015.01.007
|View full text |Cite
|
Sign up to set email alerts
|

Green synthesis and characterization of Carica papaya leaf extract coated silver nanoparticles through X-ray diffraction, electron microscopy and evaluation of bactericidal properties

Abstract: The evolution of nanotechnology and the production of nanomedicine from various sources had proven to be of intense value in the field of biomedicine. The smaller size of nanoparticles is gaining importance in research for the treatment of various diseases. Moreover the production of nanoparticles is eco-friendly and cost effective. In the present study silver nanoparticles were synthesized from Carica papaya leaf extract (CPL) and characterized for their size and shape using scanning electron microscopy and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
80
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 156 publications
(96 citation statements)
references
References 14 publications
16
80
0
Order By: Relevance
“…The data analysis showed sizes of silver nanoparticles in the range of 3-41 nm and 3-27 nm spherical shaped for SL-AgNPs and MA-AgNPs, respectively which may confer the ability to penetrate the cells/microbes and execute their bactericidal properties. Similar size ranges of AgNPs have been reported [32,33,44].…”
Section: Resultssupporting
confidence: 85%
“…The data analysis showed sizes of silver nanoparticles in the range of 3-41 nm and 3-27 nm spherical shaped for SL-AgNPs and MA-AgNPs, respectively which may confer the ability to penetrate the cells/microbes and execute their bactericidal properties. Similar size ranges of AgNPs have been reported [32,33,44].…”
Section: Resultssupporting
confidence: 85%
“…The formation of AgNPs after reduction of Ag + which was confirmed by the color changes with addition of leaf extracts of Ocimum sanctum L. to AgNO 3 solution. The synthesis and aggregation of AgNPs through the fall of time was supported the progress of latest absorbance bands at 444 nm [45]. It showed that the transfer of charges may be happened among the medium and the particles present in the solution.…”
Section: Discussionmentioning
confidence: 74%
“…20 mL of freshly prepared 0.1 M AgNO3 solution was added (drop-wise) to the flask. The flask was incubated in dark for 24 hrs at room temperature [15]. …”
Section: Methodsmentioning
confidence: 99%